PROGRAM ALOKASI DANA DESA (ADD) DALAM PENGEMBANGAN EKONOMI DI KECAMATAN MARAWOLA KABUPATEN SIGI - Nasar, M. (Katalogis, 2016)
This research intends to find out and analyze: 1) planning process, action, eveluation, and accountability of the village fund at Marawola district , Sigi regency; and 2) village allocation funds program in economic development at Marawola district , Sigi regency. This was a qualitative descriptive research with 15 informants selected through purposive sampling. The data were analyzed through data reduction, data display, and conclusion. The results show that: 1) planning process, action, and the village fund evaluation at Tinggede, Bomba, and Binangga villages run well based on the participatory development conceptÂ characterized by participatory, responsive, and transparency principles. An accountability of village allocation funds technically and administratively were effective, however in financial administration was not effective; and 2) the village fund management at the three villages in hal fulfilled the basic needs.